Analysis of The Effect of E-IKD as Data Processing on The Performance of Lecturers (Case University of Lancang Kuning) - Pandu Pratama Putra; Febrizal Alfarasy Syam; Bayu Febriadi; Didik Siswanto (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Badan Penjaminan Mutu of Lancang Kuning University (BPM UNILAK) is an agency in charge of implementing an internal quality assurance system (SPMI) and an external quality assurance system (SPME) or also known as accreditation but in processing Lecturer Performance Index (IKD) data. , still use manual data in data processing, so this causes a lot of problems. Among them: are delays in reporting, inaccurate data, lack of efficiency and effectiveness of work, overlapping data, poor data archiving, and other problems that affect all aspects of the existing assessment. To be able to answer all these challenges, the author intends to propose research on making computerized-based Quality Assurance service applications, especially in online-based Lecturer Performance Index data processing. Its purpose is to make it easier for the academic community of Lancang Kuning University in carrying out the collection of the Lecturer Performance Index. It is also hoped that the existence of a computerized-based Quality Assurance Application service will be more effective and efficient at work so that UNILAK's vision and mission are superior to the parameters that have been determined in the service system. The purpose of this research is the application of information technology-based e-IKD (Electronic Lecturer Performance Index) as a service medium for lecturers and as an evaluation medium for the Quality Assurance Agency (BPM) in all units within Lancang Kuning University. This e-IKD was created using the Mobile/Web Service application. Several actors are directly integrated with this system service, such as the Unit at Lancang Kuning University, UPM, Lecturers, and Administrators. Methodology This research uses case tools which are computer-based products, aiming to support one or more software or process engineering activities. The purpose of case tools is to increase the speed of analysis of higher education leaders, provide information related to existing business processes, increase accuracy in conducting performance evaluations, better documentation, and better presentation of information.